2015
DOI: 10.1371/journal.ppat.1005201
|View full text |Cite
|
Sign up to set email alerts
|

Peripheral Vγ9Vδ2 T Cells Are a Novel Reservoir of Latent HIV Infection

Abstract: Eradication of HIV infection will require the identification of all cellular reservoirs that harbor latent infection. Despite low or lack of CD4 receptor expression on Vδ2 T cells, infection of these cells has previously been reported. We found that upregulation of the CD4 receptor may render primary Vδ2 cells target for HIV infection in vitro and we propose that HIV-induced immune activation may allow infection of γδ T cells in vivo. We assessed the presence of latent HIV infection by measurements of DNA and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
73
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(82 citation statements)
references
References 41 publications
(52 reference statements)
9
73
0
Order By: Relevance
“…Resting memory CD4+ T cell reservoirs have been estimated to have a half-life of 44 months, meaning that their clearance during ART may take as long as 73 years [13, 17, 18]. Subsequently, distinct populations of CD4+ T cells have also been recognized to contribute to the pool of latently infected cells [1921], although those are outside the scope of the present review. The half-life of resting memory CD4+ T cell reservoirs corresponds to the long-phase decay of residual plasma viremia in persons taking long-term ART [22].…”
Section: Usual and Unusual Suspectsmentioning
confidence: 99%
“…Resting memory CD4+ T cell reservoirs have been estimated to have a half-life of 44 months, meaning that their clearance during ART may take as long as 73 years [13, 17, 18]. Subsequently, distinct populations of CD4+ T cells have also been recognized to contribute to the pool of latently infected cells [1921], although those are outside the scope of the present review. The half-life of resting memory CD4+ T cell reservoirs corresponds to the long-phase decay of residual plasma viremia in persons taking long-term ART [22].…”
Section: Usual and Unusual Suspectsmentioning
confidence: 99%
“…Similar changes in the microenvironment could possibly promote HIV replication. In an unexpected finding, recently it was shown that resting Vδ2+ cells act as reservoir for HIV [13] whereas HBMPP+IL-2 activated Vδ2+ cells could be readily infected with HIV JR-CSF in a CD4-dependent manner. Based on these findings, the study hypothesized that immune activation caused by HIV infection induces transient CD4 expression on this cell subset rendering them susceptible to HIV infection.…”
Section: Discussionmentioning
confidence: 99%
“…Natural history studies have shown a correlation between Vδ2 T cell frequency and lower vRNA [10] and reconstituted Vδ2 T-cell numbers are observed in elite controllers of HIV [11]. Cytolytic capacity of these cells against HIV-infected cells has been shown using in vitro systems [12,13]. The mucosal γδ T cells were expanded in rhesus macaques that were protected in a challenge study indicating their role in protection [14], however, these mucosal cells are primarily of Vδ1 subtype.…”
mentioning
confidence: 99%
“…In QVOA, the Poisson distribution is applied to estimate the prevalence of infected resting cells and is reported as infectious units per million (IUPM) resting CD4+ T cells. Several laboratories have used this assay to estimate the frequency of the latent infectious reservoir in different populations of cells, thus confirming that while ART significantly improves the lives of people living with HIV infection, it is ineffective against latent HIV which remains a critical barrier towards HIV eradication (Crooks et al, 2015, Soriano-Sarabia et al, 2015). With the increased effort to define modalities to eliminate persistent HIV infection, SLD assays provide an essential tool to measure the effectiveness of anti-latency interventions.…”
Section: Introductionmentioning
confidence: 88%